Phytochemical and antimicrobial screening of Hybanthus enneaspermus and Paquetina nigricense - O.A. Adegoke, T.O. Odugbemi, F.O. Awobajo, I.I. Olatunji-Bello (Recent Research in Science and Technology, 2009)
Phytochemical screening was carried out on aqueous leaf extracts of Hybanthus-enneaspermus [HE], Oldenlandia Carymbosa L [OL] and Paquetina-nigricense [PN], while antimicrobial screening was carried out on both methanolic and aqueous leaf extracts of the two plants. The result revealed the presence of Alkaloids [Flavonoids, Cyanogenic-glycosides among others], Tannin and reducing substances. The antimicrobial results showed that methanolic and aqueous leaf extract of OL possessed antimicrobial and antifungal activity as it inhibited B. subtilis, Proteus, Staphylococcus aureus, Staphylococcus albus and Candida. The methanolic and aqueous leaf extracts of PN, on the other hand also have similar effects like OL but at a different concentration. In addition, the antimicrobial activity of the two plants extracts decreases with increasing shelf life. The plants are usually used for several reasons in antenatal care by Ã‚Â Traditional Birth attendants in South west Nigeria.